BIO610: Experimental Biology: Design and Analysis / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2023)
This is an introductory subject to provide a basic knowledge of experimental design and analysis. This knowledge is required by a science major student throughout his/her scientific career in order to plan the design of experiments, to present and analyze data that is obtained and to understand statistical analysis in scientific literature. The subject emphasizes the practical rather than the theoretical aspects of statistics.